The Relationship between Organizational Conflict Strategy and Distinctive Performance (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The current research aims at identifying the relationship between conflict strategies and achieving outstanding performance, and standing at the most effective strategy for the investigation of the outstanding performance. Hence the importance of the research. The search for the problem is through a series of questions about whether there is a correlation between the search variables ,In light of this model it was built Default emerged about the hypotheses and sub-hypotheses and test the validity of the data was collected through a questionnaire tool prepared for this purpose and tested for that sample size consisted (19) members of the educational staff in the research sample schools.                                                                                                                             The Data were analyzed using a range of statistical methods and extracted results using software (SPSS) and in the light of the findings and analyzes research found a set of conclusions including that the study sample members fully agree clearly on strategies with outstanding performance, so educational organizations seeking through the realization of excellence for those of other educational organizations, and for that behave different strategies organizational conflict to reach its purpose is the most important to maintain the pillars and to consider the dealers and resources of the pillars of the approved in their organizations and finally research was presented a set of recommendations, including the training of cadres in educational institutions and provide them with the skills and knowledge necessary to diagnose organizational conflict strategies and use the best way to resolve it.